Calendar Anomalies and Risk in the Wine Exchange Market - Hooi Hooi Lean; Christine Siew Pyng Chong (Asian Academy of Management Journal of Accounting and Finance, 2012)
This paper examines calendar anomalies, in particular, the monthly effect in the international wine exchange market. The empirical findings suggest that there is a March effect for the Liv-ex Fine Wine 500 Index, a May effect for the Liv-ex Fine Wine 100 Index and the Liv-ex Claret Chip Index and a June effect for the Liv-ex Fine Wine Investables Index. We find that the market risk is higher in March and June for the Liv-ex 500 Index and the Liv-ex Investables Index, respectively. However, this higher market risk is not the cause of the monthly effect.